In search of the great Australian (graphic) novel. Issue 1 (16th February 2011) - Patrick, Kevin
The critical acclaim enjoyed by such recent Australian graphic novels as Shaun Tan's The Arrival (2006) and Nicki Greenberg's adaptation of The Great Gatsby (2007) suggested that Australia had finally 'caught up' with the United States and Britain, by embracing the graphic novel as a legitimate creative medium, on a par with literature and cinema. The media interest generated by a succession of Australian graphic novels during recent years often implied that their very existence was a relatively new phenomenon. Accepting this premise without question, however, overlooks the evolution of the graphic novel in Australia, early examples of which – such as Syd Nicholls' Middy Malone: A Book Pirates (1941) – date back to the 1940s. Documenting how historical changes in the production and dissemination of graphic novels in Australia have influenced their critical and popular reception therefore creates new opportunities to explore a largely overlooked facet of Australian print culture. Furthermore, the study of the graphic novel in an exclusively Australian context provides a new perspective for re-examining the origins, definitions and, indeed, the limitations of the term 'graphic novel', and extends the parameters of the academic literature devoted to the medium beyond the traditionally dominant Anglo-American focus.